Six frigates : - Toll, Ian W. (W.W. Norton & Co., 2006)
Starred Review. Toll, a former financial analyst and political speechwriter, makes an auspicious debut with this rousing, exhaustively researched history of the founding of the U.S. Navy. The author chronicles the late 18th- and early 19th-century process of building a fleet that could project American power beyond her shores. The ragtag Continental Navy created during the Revolution was promptly dismantled after the war, and it wasn't until 1794—in the face of threats to U.S. shipping from England, France and the Barbary states of North Africa—that Congress authorized the construction of six frigates and laid the foundation for a permanent navy. A cabinet-level Department of the Navy followed in 1798. The fledgling navy quickly proved its worth in the Quasi War against France in the Caribbean, the Tripolitan War with Tripoli and the War of 1812 against the English. In holding its own against the British, the U.S. fleet broke the British navy's "sacred spell of invincibility," sparked a "new enthusiasm for naval power" in the U.S. and marked the maturation of the American navy. Toll provides perspective by seamlessly incorporating the era's political and diplomatic history into his superlative single-volume narrative—a must-read for fans of naval history and the early American Republic